Virtual learning environments for manufacturing - Manesh, Hamed Farahani; Schaefer, Dirk (IGI Global, 2010)
Since the advent of globalization, the manufacturing industry has been subject to continuous pressure of competition. Products have to be developed faster than before, with equivalent or higher quality, and at significantly lower cost. Whilst modern manufacturing systems provide the technological edge to meet these challenges, one tends to forget that education and training of the workforce also has to be kept up-to-date. Only a workforce that is familiar with the latest advancements in the manufacturing sector and well trained in the use of state-of-the-art technology and tools will be able to effectively face the competition. Although fundamental education and training may have been provided by the academic sector, employees need to continue developing their professional skills and competencies throughout their entire professional life. One potential approach to education and training of engineers in the manufacturing sector is the utilization of Virtual Learning Environments (VLEs). Such VLEs are currently widely used for fundamental engineering education in academia, but they also hold a huge potential for successful deployment in distributed corporate settings. Manufacturing-related VLEs may provide employees at all sites of a company across the globe with an affordable and safe environment for education and training, ranging from the fundamentals of modern manufacturing to expert level training in manufacturing process planning and simulation, without any need for, or cost of, physical equipment, materials, tools or travel. In this chapter the authors discuss how Virtual Learning Environments (VLEs) for manufacturing-related education and training can be utilized in the corporate sector. © 2011 by IGI Global. All rights reserved.
Keywords: Competition; Engineering education; Personnel; Academic sectors; Education and training; Globalisation; High quality; Low-costs; Manufacturing industries; Manufacturing sector; Professional skills; State-of-the-art technology; Virtual learning environments; Personnel training